Pengaruh Social Media Marketing dan Kesadaran Terhadap Minat Berlangganan pada Layanan Streaming Vidio di Kota Surabaya - Rizky Pratama Ramadhani; Rizky Dermawan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to determine the effect of social media marketing and brand awareness on subscription intention in Vidio streaming services in Surabaya City. The population in this study are people in Surabaya City with an age range of 17 - 39 years. With a research sample of 98 respondents, namely people who have seen content or advertisements from Vidio streaming services determined by non-probability sampling method with purposive sampling technique. The method used in this research is quantitative method with SEM PLS analysis technique. The results showed that social media marketing has a positive and significant effect on subscription intention. Furthermore, brand awareness has a positive and significant effect on subscription intention.